Evaluation of Host Immune Cellular and Extracellular Matrix Responses to Prolapse Mesh With and Without Tension in a Rat Model. Issue 2 (February 2021) - Bickhaus, Jennifer A.; Fraser, Matthew O.; Weidner, Alison C.; Jayes, Friederike L.; Amundsen, Cindy L.; Gall, Ken; Marini, Frank C.; Robboy, Stanley J.; Siddiqui, Nazema Y.
Abstract : Objectives: We sought to determine whether vaginal host immune cellular and extracellular matrix responses are altered in a rat sacrocolpopexy model when lightweight polypropylene mesh is attached on tension versus without tension. Methods: We performed hysterectomy and ovariectomy in 32 Sprague-Dawley rats. Animals were assigned to 4 groups (n = 8/group): (1) controls with sham operation only (control), (2) mesh sutured only on the vagina (vaginal mesh), (3) sacrocolpopexy without tension, and (4) sacrocolpopexy with tension. Ninety days later, we excised vagina-mesh complexes. A histomorphologic scoring system of hematoxylin/eosin and Masson trichrome stained slides was used to assess host inflammatory responses. The cellular inflammatory response was further quantified using (1) identification of M1 and M2 macrophage subsets and (2) quantification of proinflammatory and anti-inflammatory cytokines. The extracellular matrix response was evaluated by measuring (1) matrix metalloproteinase-2 and matrix metalloproteinase-9 levels and (2) type I/III collagen. Results: Histomorphological tissue responses were greater in all groups with mesh compared with sham controls. Both sacrocolpopexy groups had similar scores, but each group scored significantly higher than the vaginal mesh group. Among the 4 groups, there were no statistically significant differences in M1 or M2 macrophage subsets, proinflammatory or anti-inflammatory cytokines, or extracellular matrix remodeling responses. Conclusions: Attachment of prolapse mesh resulted in an increased histologic inflammatory response independent of tension. Other markers of cellular inflammation and extracellular matrix remodeling showed no differences among experimental groups. Tension on lightweight polypropylene mesh did not significantly alter the host response in this rat sacrocolpopexy model.